Novel concept of Wilms’ tumor development: involvement of pluripotential cells of ureteric bud - Sárkány, Beatrix; Kuthi, Levente; Kovacs, Gyula (Human pathology, 2023)
It is acknowledged that nephron develops after bilateral induction of the metanephric mesenchyma and branching ureteric bud (UB), and that nephrogenic rest and Wilms’ tumor (nephroblastoma) arises from impaired differentiation of metanephric blastema. The aim of this study was to obtain more information on the involvement of UB derivatives in nephrogenic rest and Wilms’ tumor. We applied immunohistochemistry to analyze nephrogenic rests and Wilms’ tumors with mixed histology, including regressive and blastemal types. We used antibodies recognizing UB tip cells (ROBO1, SLIT2, RET), principal cells (AQP2), α- and β-intercalated cells (SLC26A4, SLC4A1, ATP6V1B1, ATP6V0D2), and their precursors (CA2). Tubules surrounded by tumorous blastemal cells resembling UB tip were positive for RET, ROBO1, and SLIT2 in Wilms’ tumor. Moreover, CA2-positive tubular structures and ATP6V1B1- and ATP6V0D2-positive immature non-α- and non-β-intercalated cells were detected in nephrogenic rest and Wilms’ tumor. We suggest that Wilms’ tumor is more than nephroblastoma and propose a definition that Wilms tumor is a malignant embryonal neoplasm derived from pluripotential cells of nephrogenic blastema and of ureteric bud tip.
Online verfügbar: 18. Mai 2023, Artikelversion: 28. Juni 2023
Gesehen am 18.08.2023